Translation and Cultural Adaptation to European Portuguese of the “Measure of Moral Distress – Healthcare Professionals” Scale: A Cross-Sectional Multicenter Study - Dias, Mónica (2022)
Introduction: Moral distress occurs when one knows the morally correct action to take but is constrained from taking that action. The aims of this study were to translate into European Portuguese and culturally adapt the “Measure of Moral Distress – Healthcare Professionals” questionnaire to the context of the Portuguese healthcare system and to explore the frequency and intensity of moral distress occurring among medical students.Material and Methods: The “Measure of Moral Distress – Healthcare Professionals” questionnaire was translated and culturally adapted to European Portuguese, following the internationally accepted “COnsensus-based Standards for the selection of health Measurement INstruments”. Afterwards, a web-based survey was conducted, following the “Checklist for Reporting Results of Internet E-Surveys” guidelines. Medical students were asked to rate potentially morally distressing situations on frequency and intensity.Results: Of approximately 4300 medical students, 939 (22%) completed the survey. Participants experienced, on average, 16 morally distressing situations. Median of composite score of moral stress was 79 (IQR 44 - 118). Only 31% of the students felt well prepared to handle a morally distressing situation, 26% considered leaving medical school and 28% thought about choosing a non-clinical specialty due to moral distress.Conclusion: Despite a plethora of studies on this topic, the results suggested that moral distress is still a common phenomenon among medical students with a cumulative effect over time. These results emphasize the importance of a critical review of medical education, reducing the harmful effects of preventable psychological phenomena in clinical practice and in the lives of future healthcare professionals.